Climate, dust, and fire across the Eocene-Oligocene transition, Patagonia - Selking, Peter A. (2015)
The Eocene-Oligocene transition (EOT) is typically interpreted as a time of drastic global cooling and drying associated with massive growth of a glacial icecap in Antarctica and the shift to an "icehouse" climate. The effects of this transition on the terrestrial environments, floras, and faunas of the Southern Hemisphere, however, have been unclear. Here we document simultaneous changes in fire regime and plant community in Patagonia, Argentina. Decreases in the concentration of magnetite in loessites from the Eocene-Oligocene Vera Member of the Sarmiento Formation correlate with decreases in the fraction of burnt palm phytoliths as well as more consistently palm-dominated phytolith assemblages. Association of magnetite and burnt palm phytoliths suggests intense wildfires, which appear to have been suppressed for ~200 k.y. shortly after the EOT. The disappearance of fire-related characteristics near the EOT is possible if changes in regional wind patterns-consistent with observed changes in sediment particle sizes-caused changes in seasonal precipitation. These results imply a more important role for fire in structuring Eocene-Oligocene landscapes than previously thought.